2016
DOI: 10.1038/srep37667
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal tuft cells regulate the ATM mediated DNA Damage response via Dclk1 dependent mechanism for crypt restitution following radiation injury

Abstract: Crypt epithelial survival and regeneration after injury require highly coordinated complex interplay between resident stem cells and diverse cell types. The function of Dclk1 expressing tuft cells regulating intestinal epithelial DNA damage response for cell survival/self-renewal after radiation-induced injury is unclear. Intestinal epithelial cells (IECs) were isolated and purified and utilized for experimental analysis. We found that small intestinal crypts of VillinCre;Dclk1f/f mice were hypoplastic and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 69 publications
3
52
0
Order By: Relevance
“…Despite this, little change was observed in tuft cell protein expression profiles. Tuft cell stability under these conditions is consistent with the long-lived nature of tuft cells relative to other differentiated intestinal cell types (16); tuft cell resistance to apoptosis following other insults, such as radiation (38), compared with other the other differentiated intestinal cell types; and the role of DCLK1-positive tuft cells in intestinal regeneration (42)(43)(44). Therefore, the enrichment of tuft cells in the intestinal epithelium after fasting is likely due to tuft cell persistence, compared with other intestinal cells, rather than proliferation of existing tuft cells.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Despite this, little change was observed in tuft cell protein expression profiles. Tuft cell stability under these conditions is consistent with the long-lived nature of tuft cells relative to other differentiated intestinal cell types (16); tuft cell resistance to apoptosis following other insults, such as radiation (38), compared with other the other differentiated intestinal cell types; and the role of DCLK1-positive tuft cells in intestinal regeneration (42)(43)(44). Therefore, the enrichment of tuft cells in the intestinal epithelium after fasting is likely due to tuft cell persistence, compared with other intestinal cells, rather than proliferation of existing tuft cells.…”
Section: Discussionmentioning
confidence: 67%
“…Other studies have observed increased oxidative stress following fasting in other organ sites (45), which can lead to increased Cox2 expression (46). Furthermore, Chandrakesan et al showed that tuft cells regulate Cox2 signaling through a DCLK1-dependent paracrine response to intestinal injury (44).…”
Section: Discussionmentioning
confidence: 99%
“…Based on Trpm5-GFP reporter, all tuft cells in intestine (63,68) and nasal cavity (75,80) express TRPM5. GNAT3…”
Section: Uea-1mentioning
confidence: 99%
“…In particular, how is the circuit regulated if IL-25 expression is constitutive, and what do tuft cells do besides secrete IL-25? Besides cytokines, tuft cells also express enzymes for eicosanoid biosynthesis, such as Cox-1, Cox-2, 5-lipoxygenase (Alox5), and hematopoietic PG-D synthase (Hpgds) (7,14,46,(66)(67)(68). How eicosanoid biosynthesis is regulated in tuft cells and the physiologic function of tuft cell-derived eicosanoids remains unknown.…”
Section: Gfi1bmentioning
confidence: 99%
“…In a study on CRC metastasis, Gao et al reported that DCLK1 expression was significantly increased in primary CRC and in lymphatic metastases compared with normal colorectal specimens, and moreover, DCLK1 mRNA levels in CRC were significantly correlated with lymph node metastasis and TNM stage (10). DCLK1 expression has also been strongly associated with EMT (18,20). Although a number of genetic studies on DCLK1 have been reported, only few reports have investigated the behavior and distribution of DCLK1 expression in human CRC tissues.…”
Section: Discussionmentioning
confidence: 99%